ANALISIS KETERAMPILAN ABAD 21 MAHASISWA PENDIDIKAN BIOLOGI FKIP UNIVERSITAS RIAU DALAM PERKULIAHAN TEKNIK DAN MANAJEMEN LABORATORIUM - Arnentis "; Yuslim Fauziah; Wiwik Asmawi (Biogenesis, 2015)
Abstract : The purpose of this research is to analyze 21st century students skill in lecture of Engineering and Laboratory Management in Biology Education Program Faculty of Teacher Training University of Riau. This research is a descriptive research with population of all students who take the subjects of Engineering and Management Laboraturium academic year 2014/2015. The sample of the study was determined by total sampling technique based on qualitative and quantitative data, the data source came from the primary data. Primary data obtained from questionnaire with the number of respondents 88 students. The parameters used are 5 elements of 21st century skills consisting of digital age literacy, inventive thinking, effective communication, high productivity and spiritual/pure values associated with the lectures of Engineering and Laboratory Management. The data collection instruments used in this research are closed questionnaire and open questionnaire. Data analysis technique used is descriptive technique. The results of the analysis of research data indicate that 21st century skills of students who take the Engineering and Management courses of Laboraturium include good category with an average of 3.91. Based on the results of the study can be concluded that students who take the course of Engineering and Management Laboraturium able to face the challenges of the 21st century. Key Words: 21st Century Skills, Engineering and Laboraturium Management Lectures, profiles